Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan di Kantor Pelayanan Perbendaharaan Sukabumi - Simangunsong, Bonse Aris Mandala Putra; Oktaviani, Lusi (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
This study aimed to determine and analyze the effect of workload and Work Stress on employee performance at the Sukabumi State Treasury Service Office. The approach used in this study is associative. The population in this study were all employees of the Sukabumi State Treasury Service Office. which amounted to 30 people, and the sample used in this study was the entire population, namely 30 people. Data collection techniques in this study used a questionnaire. Data analysis techniques in this study used the Classical Assumption Test, Multiple Regression, t-test, F-test, and the coefficient of determination. Data processing in this study used the SPSS software program (version 25.00). Partially, it is known that workload does not have a direct effect on employee performance but through work stress variables. Work stress negatively and significantly affects employee performance at the Sukabumi State Treasury Service Office. Simultaneously, it is known that workload and work stress considerably influence employee performance at the Sukabumi State Treasury Service Office.